2020
DOI: 10.1080/02701367.2019.1698698
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Physiological Responses to 120 Min. of Soccer-Specific Exercise

Abstract: Purpose: To investigate biomechanical and physiological responses to soccer-specific exercise incorporating an extra time period (ET) and assess the test-retest reliability of these responses. Methods: Twelve soccer players performed 120 min of soccer-specific exercise. Tri-axial (PLTotal) and uni-axial PlayerLoad™ in the vertical (PLV), anterior-posterior (PLA-P) and medial-lateral (PLM-L) planes were monitored using a portable accelerometer. Likewise, respiratory exchange ratio (RER) was recorded throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Indeed, tapering training loads was highly dependent on the proximity of previous and upcoming matches, as opposed to whether the team had competed in an ET period. This could have detrimental implications for recovery potentially given that biomechanical loads are increased during simulated ET matches [ 37 ]. Given their unforeseeable nature, adapting training loads in response to ET matches requires versatility and carefully orchestrated periodisation to overcome the complexities associated with maintaining aerobic fitness whilst minimising the risk of load-related injuries [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tapering training loads was highly dependent on the proximity of previous and upcoming matches, as opposed to whether the team had competed in an ET period. This could have detrimental implications for recovery potentially given that biomechanical loads are increased during simulated ET matches [ 37 ]. Given their unforeseeable nature, adapting training loads in response to ET matches requires versatility and carefully orchestrated periodisation to overcome the complexities associated with maintaining aerobic fitness whilst minimising the risk of load-related injuries [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…65 Considering distances and speeds are standardised (both across time periods and between participants), gives researcher assurance that within-exercise changes observed in a given measure are likely due to fatigue, rather than pacing or player motivation. 66 It must also be considered that treadmills are essential for certain types of research, for example studies involving climate chambers 51 or when a controlled model is required. Thought must also be applied to employing a pseudorandom activity simulation to ensure players are unable to predict upcoming speed changes, thus, imitating the stochastic distribution of match-play.…”
Section: Motorised Treadmill-based Soccer-specific Exercise Protocolsmentioning
confidence: 99%
“…This could impede natural running mechanics 67 , coupled with fatigue-induced compensatory adjustments in gait, possibly increasing soft-tissue injury-risk. 66 However, motorised treadmill simulations are also generally less effective for eliciting valid physiological data (as evidenced by small changes in biochemical milieu) 65 , sprinting speeds are not always reached and the treadmill itself can be expensive versus the cost-effectiveness of field-based simulations. All motorised-treadmillbased simulations included in this section are characterised in Table 3.…”
Section: Motorised Treadmill-based Soccer-specific Exercise Protocolsmentioning
confidence: 99%
“…A few studies have examined the physiological effects of extra time in soccer. For example, Field et al ( 13 ) reported decreased mechanical efficiency and increased fat oxidation during extra time using a simulated soccer protocol. Others, using simulated models and both peripheral nerve and transcranial magnetic stimulations, showed an exacerbated neuromuscular fatigue response to extra “playing” time ( 14 ).…”
mentioning
confidence: 99%